Spiritual growth as an impulse to self-development in the students’ living space [Духовный рост как импульс к саморазвитию в жизненном пространстве студенчества] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна; Padoan, Ivana Maria; Падоан, Ивана Мария (Харьков : ХНУ, 2005)
В рамках гуманистического образования в данной статье рассматривается личность студента и раскрывается один из путей его духовного развития. Устанавливается и анализируется зависимость между степенью осознанности студента в выборе профессии и стремлением к самореализации и духовному росту. Выявлено достаточно четкое опосредованное влияние усвоенного ранее кросс-культурного опыта на формирование у студентов эмоционально окрашенной картины будущего саморазвития. In the framework of the humanity education the student’s personality is studied in this paper as well as one of the ways of its spiritual development is revealed. In this way, a special dependence between the student’s cognition degree in own professional choice and its aspiration to both the self-realization and spiritual advance is established and analyzed. The influence of the cross-cultural previous experience to the formation of emotionally bright picture of the student’s future self-development was discovered.
Keywords: духовный рост; кросс-культурный опыт; систематизация; итальянский; spirituality; cross-culturalexperience; systematization; Italian